2008
DOI: 10.1111/j.1440-1681.2008.04970.x
|View full text |Cite
|
Sign up to set email alerts
|

DENGUE FEVER ACTIVATES THE l‐ARGININE–NITRIC OXIDE PATHWAY: AN EXPLANATION FOR REDUCED AGGREGATION OF HUMAN PLATELETS

Abstract: In patients with Dengue fever, a viral inflammatory syndrome, haemorrhage is a significant pathological feature, yet the underlying mechanisms remain unclear. Nitric oxide (NO) is an important regulator of platelet function, inhibiting aggregation, recruitment and adhesion to the vascular endothelium. We have investigated whether changes in the activity of the L-arginine-NO pathway in human platelets may account for increased bleeding in patients with Dengue fever. A total of 16 patients with Dengue fever and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Previous reports have shown that agonist-induced platelet aggregations are reduced in platelets pre-treated with heat in vitro or in platelets from patients with fever and heatstroke [5,22]. To explore the effect of hyperthermia on platelet function, PRP was isolated and incubated at hypothermia (22 C), normothermia (37 C) or hyperthermia (40 or 42 C) for 1 or 2 h, and then induced to aggregation by ADP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that agonist-induced platelet aggregations are reduced in platelets pre-treated with heat in vitro or in platelets from patients with fever and heatstroke [5,22]. To explore the effect of hyperthermia on platelet function, PRP was isolated and incubated at hypothermia (22 C), normothermia (37 C) or hyperthermia (40 or 42 C) for 1 or 2 h, and then induced to aggregation by ADP.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet count obviously reduces in most patients with dengue fever [4] or heatstroke [1]. And reduced platelet aggregations have been found in patients with hemorrhage fever [5], raising the possibility that fever or hyperthermia incurs reduction of platelet count or function leading to hemorrhage. Fever or hyperthermia induces a series of physiological responses including cell apoptosis in human body [1,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal platelet homeostasis involves anti‐aggregatory NO and pro‐aggregatory thromboxane (TX) A 2 13 . Mendes‐Ribiero et al 2 . observed increased NO activity, consistent with the anti‐aggregatory and haemorrhagic tendency in DHF/DSS.…”
mentioning
confidence: 54%
“…In this issue of the journal, Mendes Ribeiro et al . have implicated the l ‐arginine–NO pathway in the pathophysiology of dengue haemorrhagic fever/dengue shock syndrome (DHF/DSS) 2 …”
mentioning
confidence: 99%